Financial development, remittances and economic growth: A threshold analysis - James Atta Peprah; Isaac Kwesi Ofori; Abel Nyarko Asomani (Cogent Economics & Finance, 2019)
Sources of economic growth in Ghana have not been clear. Several studies have contributed to the finance and growth literature with little attention on remittances and the joint effect of financial sector development and remittances. This paper uses macrodata to examine the linkages between financial development, remittances and economic growth in Ghana. We estimate a dynamic heterogeneous Autoregressive Distributed Lag (ARDL) model to show that financial booms are not, in general, growth-enhancing, and a certain level of financial development can drag down economic growth in the long term and the combined effect of financial development and remittances should be of concern to policymakers.
Keywords: F22; F43; O16; O40; 330; Economics; Political Economy; Finance; Business; Management and Accounting; Industry & Industrial Studies